Behavior analysis in education - Ralph Gardner III (Brooks/Cole Pub. Co., 1994)
This reader summarizes the major issues, trends, and findings found in behavior analysis in education literature. The contributors are leaders in the behavior analytic field, and their chapter-length treatment of topics, such as the Future of Behavior Analysis in Education, Early Childhood Interventions, and Promoting Applied Behavior Analysis, provides a volume that allows the professor to cover a range of topics which emphasize measurably superior instruction